Influence of sharpening filters on the detection of root fractures using low-dose cone-beam computed tomography - González, Alexandra Robles; Tosoni, Guilherme Monteiro [UNESP]; Freitas, Deborah Queiroz; Oliveira, Matheus L. (Springer Nature, 2022)
Objectives: To evaluate the influence of sharpening filters in the detection of root fractures using low-dose cone-beam computed tomography (CBCT). Materials and methods: Eighty-four CBCT volumes acquired at three mA levels of 28 teeth inserted in the dental socket of dry human skull were selected from a previous study. The teeth were divided into four groups according to the presence and absence of root fracture and endodontic filling. Five radiologists evaluated all CBCT volumes for the presence of root fracture with and without the application of “Sharpen 1x” and “Sharpen 2x” filters in OnDemand3D software. Area under the ROC curve (AUC), sensitivity, specificity, and inter- and intra-observer concordance were calculated and compared (α = 0.05). Results: Sharpening filters did not lead to significant differences in AUC, sensitivity, and specificity at the three mA levels tested (p > 0.05), regardless of the presence of endodontic filling (p > 0.05). However, the significant reduction of AUC observed in CBCT volumes at 4 mA without filter (p < 0.05) ceased to exist after the application of filters (p > 0.05). Sensitivity and specificity ranged from low and moderate. Conclusions: The use of sharpening filters can be recommended in CBCT volumes at 4 mA for root fracture detection for leading to the same performance as those at 6.3 and 10 mA. The presence of endodontic filling material did not influence the action of filters in the diagnosis of root fracture. Clinical relevance: Sharpening filters seem to contribute to the diagnosis of root fracture in CBCT volumes acquired with reduced radiation dose.
Keywords: Cone-beam computed tomography; Diagnostic imaging; Radiographic image enhancement; Tooth fractures